Exploration of Indonesia’s Culture through Batik as an Idea for the Creation of Contemporary Calligraphy Paintings - Suci Rahmadani Br Padang; Ayu Astriani; Adek Cerah Kurnia Azis (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
Batik is one of Indonesia's cultural heritages that has a distinctive visual character, complex motif structure, and philosophical values that reflect local wisdom. The integration of batik motifs into contemporary calligraphy paintings offers a new aesthetic approach in exploring Nusantara culture through the medium of modern art. This study aims to: (1) identify and determine relevant batik motifs that maintain cultural values; (2) describe the artistic and technical processes in creating contemporary calligraphy paintings based on batik motifs; and (3) evaluate the final results from the aesthetic and cultural representation aspects. The study uses the I Made Bandem creative method which includes the stages of preparation, elaboration, synthesis, concept realization, and completion. The synthesis stage is an important part in combining the character of calligraphy lines with the structure of batik motifs, thus forming a balanced, harmonious composition with symbolic depth. The results of the study show that batik motifs not only serve as supporting ornaments, but can also function as structural elements that enrich the visual rhythm, space, and meaning in contemporary calligraphy works. The conclusion of the study confirms that the incorporation of batik motifs in contemporary painting can be a means of cultural preservation while expanding the visual vocabulary of modern art. The novelty of the work lies in the visual synthesis strategy that places batik motifs as generative elements in the calligraphy system, providing practical implications for the development of culture-based art in the future.